Quantification of the Effect of Pressure Wire Drift on the Diagnostic Performance of Fractional Flow Reserve, Instantaneous Wave-Free Ratio, and Whole-Cycle Pd/Pa. (April 2016) - Cook, Christopher M.; Ahmad, Yousif; Shun-Shin, Matthew J.; Nijjer, Sukhjinder; Petraco, Ricardo; Al-Lamee, Rasha; Mayet, Jamil; Francis, Darrel P.; Sen, Sayan; Davies, Justin E.
Abstract : Background—: Small drifts in intracoronary pressure measurements (±2 mm Hg) can affect stenosis categorization using pressure indices. This has not previously been assessed for fractional flow reserve (FFR), instantaneous wave-free ratio (iFR), and whole-cycle distal pressure/proximal pressure (Pd/Pa) indices. Methods and Results—Four hundred forty-seven: stenoses were assessed with FFR, iFR, and whole-cycle Pd/Pa. Cut point values for significance were predefined as ⩽0.8, <0.90, and <0.93, respectively. Pressure wire drift was simulated by offsetting the distal coronary pressure trace by ±2 mm Hg. FFR, iFR, and whole-cycle Pd/Pa indices were recalculated and stenosis misclassification quantified. Median (±median absolute deviation) values for FFR, iFR, and whole-cycle Pd/Pa were 0.81 (±0.11), 0.90 (±0.07), and 0.93 (±0.06), respectively. For the cut point of FFR, iFR, and whole-cycle Pd/Pa, 34.6% (155), 50.1% (224), and 62.2% (278) of values, respectively, lay within ±0.05 U. With ±2 mm Hg pressure wire drift, 21% (94), 25% (110), and 33% (148) of the study population were misclassified with FFR, iFR, and whole-cycle Pd/Pa, respectively. Both FFR and iFR had significantly lower misclassification than whole-cycle Pd/Pa ( P <0.001). There was no statistically significant difference between the diagnostic performance of FFR and iFR ( P =0.125). Conclusions—: In a substantial proportion of cases, small amounts of pressure wire drift are enough to cause stenoses to change classification. Whole-cycle Pd/Pa is more vulnerable to such reclassification than FFR and iFR.